Prescription opioid injection among young people who inject drugs in New York City: a mixed-methods description and associations with hepatitis C virus infection and overdose - Pedro Mateu-Gelabert; Honoria Guarino; Jon E. Zibbell; Jennifer Teubl; Chunki Fong; Elizabeth Goodbody; Brian Edlin; Carli Salvati; Samuel R. Friedman (BMC, 2020)
Abstract Aim Evidence is emerging that prescription opioid (PO) injection is associated with increased health risks. This mixed-methods study compares the mechanics of PO and heroin injection and examines the demographic and drug-related correlates of lifetime PO injection in a sample of young people who inject drugs (PWID) in New York City (NYC). Methods Qualitative analysis of 46 semi-structured interviews with young adult opioid users ages 18-32. Interview segments describing PO injection were analyzed for common themes. Quantitative analysis of structured interviews with 539 young adult opioid users ages 18-29 recruited via respondent-driven sampling (RDS). Analyses are based on the subsample of 353 participants (65%) who reported having ever injected drugs. All variables were assessed via self-report, except hepatitis C virus status, which was established via rapid antibody testing. Results Participants described injecting POs and reported that preparing abuse-deterrent pills for injection is especially cumbersome, requiring extended manipulation and large amounts of water. Injecting POs, in contrast to injecting heroin, requires repeated injections per injection episode. Among RDS-recruited participants, the majority of injectors reported injecting POs, sporadically (33%) or regularly (26%), but often infrequently (≤ 7 days/month). In separate multivariable analyses controlling for syringe- and cooker-sharing, ever injecting POs was a significant predictor of testing HCV antibody-positive (AOR = 2.97) and lifetime experience of non-fatal overdose (AOR = 2.51). Ever injecting POs was independently associated with lifetime homelessness (AOR = 2.93) and having grown up in a middle-income ($51,000-100,000/year vs. ≤ $50,000/year; AOR = 1.86) or a high-income household (> $100,000/year vs. ≤ $50,000/year; AOR = 2.54). Conclusions Even in an urban environment like NYC with widespread heroin access, most young PWID have injected POs, although less frequently than heroin. PO injection involves practices that are known to increase risk for blood-borne viral infection (e.g., repeated injections) and predicted testing HCV-positive, as well as overdose. PO injection may also serve as a marker for a subgroup of PWID at elevated risk for multiple drug use-related comorbidities. Programs that provide prevention services to PWID need to tailor harm reduction measures and messaging to the specific practices and harms associated with the injection of POs.